The Soar Approach: A Strategy to Improve the Competition of Halal Culinary MSMEs Based on Digital Technology - Salwa, Faridah; Syahbudi, Muhammad; Nasution, Muhammad Lathief Ilhamy (Universitas Trunojoyo Madura, 2024)
The aim of this research is to determine the optimal approach for enhancing the competitiveness of halal culinary products.This research is qualitative research using quantitative tools, namely by using the SOAR (Strengths, Opportunities, Aspirations, and Results) method. The data collection technique uses questionnaires and interviews. The results of the questionnaire were then processed using SOAR matrix analysis in 3 stages: identifying SOAR factors, determining IFE and EFA values, and determining strategy results using SOAR diagram matrix. The subject of this research is Tanjungbalai halal culinary MSMEs, while the object of this research is a strategy to increase competitiveness. The respondents to this study are all halal culinary MSME sellers in Tanjungbalai.The result of the SOAR method is SA, which is a strategy that uses all aspirations to increase the competitiveness of halal culinary MSME sales. Strength Aspirations Strategy. The strategy carried out is to improve product quality, improve the quality of labels and packaging, and diversify marketing.